2011
DOI: 10.1177/004005991104300601
|View full text |Cite
|
Sign up to set email alerts
|

A Visually Based Intervention for Children with Autism Spectrum Disorder

Abstract: Visually based interventions such as video modeling have been demonstrated to be effective with students with autism spectrum disorder. This approach has wide utility, is appropriate for use with students of a range of ages and abilities, promotes independent functioning, and can be used to address numerous learner objectives, including behavioral, self-help, communication, and social objectives. What are the components of video modeling? What's the best way to implement video modeling with students? Do the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…First, it is possible that the present study's specific video modeling strategies were not effective and/or did not provide participants with ASD with enough information. While past studies' recommendations were used in the creation of the present study's video modeling procedures (Bellini & Akullian, 2007;Ganz, Earles-Vollrath, & Cook, 2011;McCoy & Hermarisen, 2007;Shukla-Mehta et al, 2010;Wilson, 2013), small differences within duration of videos, overall presentation, and/or the general research field may have caused video modeling to be less effective within motor assessment settings. For example, previous studies have suggested video clip lengths of 3-5 minutes and multiple viewings and/or sessions for social, behavioral, communicative and play skills (Bellini & Akullian, 2007;Shukla-Mehta et al, 2010), with effective interventions using videos as short as 30 seconds (Bellini & Akullian, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is possible that the present study's specific video modeling strategies were not effective and/or did not provide participants with ASD with enough information. While past studies' recommendations were used in the creation of the present study's video modeling procedures (Bellini & Akullian, 2007;Ganz, Earles-Vollrath, & Cook, 2011;McCoy & Hermarisen, 2007;Shukla-Mehta et al, 2010;Wilson, 2013), small differences within duration of videos, overall presentation, and/or the general research field may have caused video modeling to be less effective within motor assessment settings. For example, previous studies have suggested video clip lengths of 3-5 minutes and multiple viewings and/or sessions for social, behavioral, communicative and play skills (Bellini & Akullian, 2007;Shukla-Mehta et al, 2010), with effective interventions using videos as short as 30 seconds (Bellini & Akullian, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the effect of video modeling on motor skill assessment performance for children with ASD remains inconclusive. Although there is a variety of literature that provides evidence-based recommendations for creating video modeling interventions in academic, social and behavioral fields of research (Bellini & Akullian, 2007;Ganz et al, 2011;Shukla-Mehta et al, 2010;Wilson, 2013), and recent suggestion-based papers suggest for the use of video modeling in physical education and assessment (Case & Yun, 2015;Obrusnikova & Rattigan, 2016), there are currently no studies that empirically support the use of video modeling strategies to improve motor skills among children with ASD. It is therefore the recommendation of these authors that present and future studies examining video modeling within motor assessment and physical education are offered in the literature, regardless of the outcome, with detailed accounts of the included methodology.…”
Section: Perspectivesmentioning
confidence: 99%
“…Особе с аутизмом су успешније у перципирању и обради визуелних него аудитивних стимулуса (Cohen, 1998;Ganz et al, 2011;Hodgon, 1995). У складу с тим сазнањима приступи у раду с особама с аутизмом врло се често базирају на визуелним стратегијама.…”
Section: полазне теоријске основе истраживањаunclassified
“…People with AS are considered to have a good visual perception (Ganz et al, 2011;Rao & Gagie, 2006,) and generally find processing visual cues easier than verbal cues (Hume et al, 2009). Our study shows that the use of photos through projector or Picasa and use of video clips encourages and helps develop a class discussion.…”
Section: Using Photos and Visual Processing Assistive Technologiesmentioning
confidence: 99%
“…Because many students with AS are described as visual learners (Ganz, Earles-Vollrath, & Cook, 2011;Rao & Gagie, 2006) they tend to show improved response to information presented visually. By using a student's visual processing strength, these strategies can help decrease reliance on areas of deficits, such as auditory processing and communication.…”
Section: Introductionmentioning
confidence: 99%